Social policy review. - Farnsworth, Kevin; Irving, Zoe; Fenger, Menno (Social Policy Review., 2014)
Since the 2008 economic crisis, each year has brought new challenges to welfare states. This important annual volume with contributions from an exciting mix of internationally renowned experts within the social policy community examines the economic and political challenges that have confronted governments, and highlights the diverse ways in which nations have responded. Part One explores the most pressing questions confronting British social policy, from the school-leaving age, employment, in-work benefits to taxation. Part Two examines the political and professional dilemmas involved in the delivery and financing of social policy. Part Three identifies the challenges in integrating social policy with other areas of the welfare state, including social care, health policy and labour market policy. This comprehensive discussion of the most challenging issues arising during the past year provides academics and students with an invaluable up-to-date analysis of the current state of social policy.